SIKAP INTEGRASI NASIONAL DITINJAU DARI PEMAHAMAN NILAI-NILAI SEJARAH DAN SIKAP SOSIAL SISWA - Rohim, Muhammad Nur; Suryani, Nunuk; Pelu, Musa (Candi, 2017)
The objectives of research were: 1) to find out the relationship between understanding of historical values with attitude of national integration of the students of class XI IPS SMA Negeri Gondangrejo year 2016/2017. 2) to find out the relationship between social attitude with attitude of national integration of the students of class XI IPS SMA Negeri Gondangrejo year 2016/2017. 3) to find out the relationship between understanding of historical values and social attitude simultaneously with attitude of national integration of the students of class XI IPS SMA Negeri Gondangrejo year 2016/2017.This research employed quantitative method with correlational research design. The population of research was all of the XI IPS students of SMA Negeri Gondangrejo year 2016/2017. Constinting of 130 students. The sample used  in this study consisted of 98 students. The sample was taken using random sampling technique. Technique of collecting data used were test and questionnare. Technique of analyzing data used in this study were correlational and regression analyses.The conclusions of research were as: 1) there is a positively relationship between understanding of historical values with attitude of national integration of the students of class XI IPS SMA Negeri Gondangrejo year 2016/2017. It could be seen from the multiple linear regression analysis showing that tstatistic> ttabel, 2,069>1,664 and significance value 0,039< 0,05 with relative contribution of1,34 %  andeffective contribution of 0,89%. 2) there is a positively relationship between social attitudes with attitude of national integration of the students of class XI IPS SMA Negeri Gondangrejo year 2016/2017. It could be seen from the multiple linear regression analysis showing that tstatistic> ttabel,13,598>1,664 and significance value 0,00< 0,05 with relative contribution of98,68% andeffective contribution of 65,33%. 3) there is a positively relationship between understanding of historical values and social attitude simultaneously with attitude of national integration of the students of class XI IPS SMA Negeri Gondangrejo year 2016/2017. It could be seen from the multiple linear regression variance analysis showing that Fstatistic>Ftabel,93,156>3,090and significance value 0,00< 0,05. The coefficient of determination (R2) of 0,662 indicated that understanding of historical values and social attitude  affected 66,2 % attitude of national integration of students XI IPS SMA Negeri Gondangrejo year 2016/2017, while the rest affected by other variables.